Crystal structure and vibrational spectra of Ln1-xErxFeO3 (Ln =Gd or Sm, x = 0; 0.2 or 0.4) - Popovska, Sofija; Dimitrovska-Lazova, Sandra; Bukleski, Miha; Skalar, Tina; Aleksovska, Slobotka (My University, 2024)
In recent years, perovskites that contain two different lanthanides in the A-position have garnered significant attention due to the ability of these elements to introduce exceptional properties and functionalities to the versatile perovskite framework. Continuing our work on complex perovskites, in this work the results of synthesis, crystal structure, detailed crystallochemical calculations, morphology, and detailed vibrational properties of new complex perovskites with general formula Ln1–xErxFeO3 (Ln =Gd, Sm; x =0; 0.2 and 0.4) are presented. These perovskites were synthesized using the combustion sol-gel method, employing citric acid as a fuel, and controlled temperature and pH conditions during the initial mixture preparation. X-ray powder diffraction was utilized to identify the obtained perovskites, and their crystal structures were refined using the Rietveld method. The X-ray diffraction patterns revealed that these perovskites are orthorhombic and crystallize within the space group Pnma. Crystal structure refinement and calculations of certain crystallographic parameters indicated that the primary cause of deviation from the ideal perovskite structure is octahedral tilting. Тhis distortion is more pronounced when erbium, a smaller ion, replaces the larger gadolinium and samarium in the perovskite lattice. Moreover, a higher erbium content increases the deformation of the polyhedron around the A-cation. In order to determine how the applied method of synthesis affects the morphology and dimensions of the particles of the obtained powders, SEM images were recorded. It can be noticed that the morphology of the compounds within the series is similar, i.e. the particles exhibit nanoscale dimensions and have a porous, spongy appearance. The recorded infrared and Raman spectra of the substituted perovskites confirmed the partial substitution of gadolinium/samarium with erbium. The incorporation of the smaller Er3+in the place of the larger Gd3+and Sm3+ leads to a reduction in the lattice parameters causing a shift of the vibrational modes towards higher wavenumbers.
Keywords: Lanthanide perovskites Sol-gel method X-ray powder diffraction Scanning electron microscopy Infrared spectroscopy Raman spectroscopy